Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Synthesis and biological evaluation of some bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline and its amide derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh (Journal of Chemical Sciences, 2018)
In the present investigation, a series of bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline analogues were synthesized and characterized by IR, NMR (1H and 13C) and mass spectra. All newly synthesized 15 compounds were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra in both active and dormant state using an established XTT Reduction Menadione assay (XRMA). The titled compounds exhibited minimum inhibitory concentration (MIC90) ranging from 0.05 to >30 (μg/mL). The potent four compounds were further evaluated in THP-1 infection model where they demonstrated significant antitubercular activity. All the ex vivo active were further evaluated for cytotoxic activity against THP-1, MCK7 and HeLa cell lines in order to check selectivity index. All compounds were further screened against four different bacteria to assess their selectivity towards MTB. These derivatives could be considered as a precursor structure for further design of antituberculosis agent.
Keywords: 4-dimethylphenylthio)phenyl] aniline; antituberculosis activity; Cytotoxicity; [2-(2

Ultrasound assisted synthesis of 4-(Benzyloxy)-N-(3-chloro-2-(substitutedphenyl)-4-oxoazetidin-1-yl) benzamide as challenging anti-tubercular scaffold - Nimbalkar, Urja D.; Seijas, Julio A.; Borkute, Rachna; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Sarkar, Dhiman; Nikalje, Anna Pratima G. (Molecules, 2018)
A series of ten novel derivatives of 4-(benzyloxy)-N-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl) benzamide 6a-j were synthesized in good yield from the key compound 4-(benzyloxy)-N-(substituted benzylidene) benzo hydrazide, called Schiff `s bases 5a-j, by Staudinger reaction ([2 + 2] ketene-imine cycloaddition reaction) with chloro acetyl chloride in the presence of catalyst tri ethylamine and solvent dimethyl formamide (DMF), by using ultra-sonication as one of the green chemistry tools. All the synthesised compounds were evaluated for in vitro anti-tubercular activity against Mycobacterium tuberculosis (MTB) and most of them showed promising activity with an IC50 value of less than 1 mu g/mL. To establish the safety, all the synthesized compounds were further tested for cytotoxicity against the human cancer cell line HeLa and all 6a-j compounds were found to be non-cytotoxic in nature. The molecular docking study was carried out with essential enzyme InhA (FabI/ENR) of Mycobacterium responsible for cell wall synthesis which suggests that 6a and 6e are the most active derivatives of the series. The theoretical evaluation of cell permeability based on Lipinski's rule of five has helped to rationalize the biological results and hence the synthesized azetidinone derivatives 6a-j were also analyzed for physicochemical evaluation that is, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties and the results showed that all the derivatives could comply with essential features required for a potential lead in the anti-tubercular drug discovery process.
Keywords: ADMET study; anti-tubercular screening; azetidinone; cytotoxicity study; green chemistry; Molecular docking; ultra-sonication